Developing Contextual-Based Worksheets on Prism and Pyramid for Junior High School Students - Wisnu Siwi Satiti; Deandra Putri Damayanty (APPLICATION: Applied science in Learning Research, 2022)
Students’ understanding and mastery in determining the surface area and volume of geometric shapes, especially flat-sided shapes, is an important ability due to many applications of it in real life. The concepts of surface area and volume not only expand students' understanding of spatial measurements, but also can develop students' understanding in multiplication, fraction, algebraic multiplication and dilation. However, based on results of previous studies, difficulties often faced by students in solving surface area and volume problems which are related to conceptual errors. Many students also have difficulties in understanding and applying concepts and skills involving this concept. Therefore, teachers should select and use relevant teaching materials. One of them is that teachers can arrange teaching materials consisting of several activities that can be made in the form of worksheets that can help students build knowledge independently. One form of teaching materials that can be developed in order to meet this need is the Student Worksheet (LKPD). Therefore, this research is about the development students’ worksheet in Prism and Pyramid concept within contextual problems for VIII grade students. The type of research used is Research and Development (R&D) research, by adapting ADDIE model. The results show that the Prism and Pyramid worksheet within contextual problems are valid and practical. Besides that, the results of the implementation of the Contextual-Based Worksheets on Prism and Pyramid in this study showed that the use of context-based worksheets effectively helps students understand the mathematics material.